Friday

December 19, 2014

December 19, 2014

Posted by **Jennifer** on Sunday, January 1, 2012 at 6:01pm.

- College Algebra -
**Steve**, Sunday, January 1, 2012 at 6:49pmwhat's the problem? Just plug and chug:

f(g) = ln(g-1) = ln(1+e^x-1) = ln(e^x) = x

g(f) = 1+e^f = 1 + e^(ln (x-1)) = 1 + x-1 = x

Just keep in mind the definition of a logarithm:

e^lnx = x

ln e^x = x

**Answer this Question**

**Related Questions**

College Algebra - Verify the function f and g, are inverses of each other by ...

College Algebra - Verify that the function f and g, are inverses of each other ...

math - verify that the function f and g are inverse of each other by showing f(g...

algebra - Verify that the functions f and g are inverses of each other by ...

Precalculus - Verify that the functions f and g, are inverses of each other by ...

pre calculus - verify functions f and g are inverses of each other by showing ...

precalculus - verify the functions are inverses of each other by showing that f(...

Algebra/Precalculus - How can I verify that f(x)=(x+3)/(x-2)and g(x)=(2x+3)/(x-1...

math - verify that f and g are inverse functions. f(x) = 5x^2 x>(or equal too...

Advanced Algebra - What is the inverse of each of the functions defined by the ...